The Essence of Creation of Allah’s Creatures Through Tafakur: Study of Takhrij and Syarah Hadith - Fadhilah, Lindiani Nur; Taher, Ahmad Tarmizi (Journal of Takhrij Al-Hadith, 2023)
This study aims to discuss the hadith about the creation of creatures. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the creation of creatures in the history of Bukhari No. 2955. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi meets the qualifications of maqbul ma’mul bih for Islamic practice. This study concludes that the hadith narrated by Bukhari No. 2955 is relevant to be used as motivation and enthusiasm in efforts to increase faith through tafakur activities to understand the essence or purpose of God’s creation.